Pengembangan Media Big Book untuk Meningkatkan Hasil Belajar Materi Pecahan Kelas II Madrasah IbtidaiyahÂ - Yuni Kurniawati; Sumaji Sumaji; Fitri Budi Suryani (Balai Diklat Keagamaan Semarang, 2023)
The aims of this study were 1) to find out whether the big book media is suitable for fractional material for class II MI students in Rembang Regency. 2) to find out whether or not the ledger of fraction material in class II MI Rembang Regency can be implemented. 3) To find out how well the fractional data of class II MI students in Rembang Regency is processed using ledger media. This research strategy uses experimental product testing in conjunction with quantitative R&D methods. gather information from tests, especially protests and pretests. The steps taken in this study are as follows: 1) Issues and possibilities; 2) Obtain data; and 3) Product design. 4) Perform expert product evaluations. 5) Make the product better or change it. 6) Field tests and 7) Preparation of reports Data analysis using descriptive analysis. Results of analysis and research results (a) Big book media made of fractional material meets the requirements for use (c) This shows that the experimental group using bigbook media was more successful than the control group in improving learning outcomes in fractional material.